The effect of teaching physics using the Pressly model on second intermediate students' learning of reflective thinking skills (Journal of the College of Basic Education, 2022)
This current search aimed to acquaintance of effect " The Effect of Teaching Physics by Pressly's Model of Second year intermediate male Students for learn Skills for Reflective Thinking . For checking from the search aim ،the two researchers put a hypothesis of zero ، its content : There is no significant difference at (0،05) level between the mean scores of the experimental group students who were taught according to the Pressly and the mean scores of the control group students who are taught according to the conventional method in Test reflective thinking. The current research community specified by the students mail of Second grade on intermediate school in Bob Al-Sham intermediate school for boys for the academic year (2014-2015) amounting (255 students ) distributed on for classes ( a، b، c، d، e )using the experimental and control groups ، one control the other restraint partially with post-test to measure achievement ، the processes of science randomly on the five classes (a، b ، c ، d، e) the appointment of random selected Divisions (c ، d) two sets of search ، as randomly assigned (d ) to be a control group ، and (c ) an experimental group. After set aside the failures the students number at the two groups (92) demanded by (46) students of the experimental group and 46 students for the control group ، rewarded groups in the variables (intelligence، previous information ، former educational achievements، test reflective thinking)، the scientific object identified by The last four chapters of the Physics book Sixth edition for the academic year 2014 ، applied experience in the second semester of the academic year (2014-2015)، and the researcher taught the two sets of research by himself and prepared lesson plans necessary which was (18) plan the experimental group ، and the same for the control group formulated behavioral objectives for the four chapters، The tools of the research include test to measure testing of reflective thinking content of (20) objective items of multiple Skills representing (Moditation Andobservation، Paral ogisms rerealing، ، Conclusions، Provide Convincing explanations، Proposed solutions )، they were verified of its veracity، stability and the coefficient of difficulty، and showed the results of research using (Z-test) for two independent samples which was equal size to the following : The superiority of the experimental group who studied according to Pressly on the learning control group students who studied according to the usual way to test testing of reflective thinking، From the results the research has concluded that the teaching by using pressly model has a effect in reflective thinking. the volume effect (0.07) for thinking reflective. In the light of that the researcher has set a number of recommendations and suggestion conserving the results of the study.